The Nutritional Issue of Older People Receiving Home-Delivered Meals: A Systematic Review - Fleury, Ségolène; Tronchon, Paul; Rota, Juliane; Meunier, Charlotte; Mardiros, Oliver; Van Wymelbeke-Delannoy, Virginie; Sulmont-Rossé, Claire (Frontiers in Nutrition, 2021)
Background: Setting up a home-delivered meal service often allows older people suffering from physical and/or cognitive disabilities to stay at home. However, older people who delegate their food activities (food purchasing, cooking…) have been reported to have a worse nutritional status than people who take care of their food activities. In this context, we will conduct a systematic review of all studies related to the nutritional issue in home-delivered meal older recipients. Methods: In June 2020, we searched 3 databases (Pubmed, Web of Science, EMBASE) to identify studies from all years on older adults at home and receiving home-delivered meal services (population). The following outcomes were considered: nutritional status (Body Mass Index, weight, undernutrition) and nutritional intake. Any nutritional intervention, comparator, and study design were relevant for inclusion. Results: Forty-eight original studies met the inclusion criteria, most of them being published after the year 2000 (n = 34) and undertaken in the USA (n = 32). The selection includes 30 cross-sectional and 18 longitudinal studies. The main findings of this review are the following: (1) home-delivery meal older recipients are at high risk of undernutrition; (2) providing home-delivery meals may improve the nutritional status and nutrient intake; (3) this improvement is even higher when the home-delivery meal service is improved, for instance by providing dietetic counseling or adding supplementary snacks/meals or enriched food. However, even an improved service does not allow all the older recipients meeting their recommended nutritional allowance. Conclusion: This review reveals a need to further develop strategies allowing home-delivery meal older recipients to fulfill their nutritional needs. From a methodological point of view, there is a need to describe in more detail the home-delivered services provided to studies' participants to better consider meal frequency and meal content in the results.